Pengaruh Latihan Pernapasan Pursed Lips Terhadap Saturasi Oksigen pada Pasien dengan Gangguan Pernapasan di Ruang IGD RSUD Kota Mataram - Prasati, Supriana; Putra, Ageng Abdi; Suhartiningsih, Suhartiningsih; Wijaya, Alwan; Mentari, Ika Nurfajri; Ustiawaty, Jumari (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Respiratory disorder has very high prevalence in Mataram District hospital in January to May 2018. They are 326 cases of patients with respiratory disorder. One of treatments for patiens with respiratory disorder is pursed lips breathing (PLB). This research is aimed at determining the effect of training of pursed lips breathing on oxygen saturation of patients with respiratory disorder in emergency room of Mataram District Hospital. This research is pre-exsperimental study with two group pre-test post-test design. The samples were selected through non-probality accidental sampling. The data were analyzed with paired-test using SPSS 16. The data were collected through observation and pulse Oxymetry. Based of study found ther is effect of pursed lips breathing on oxygen saturation in patients with respiratory disorder in Mataram District hospital. It is inferred that there is effect of providing pursed lips breathing on oxygen saturation of patients with respiratory disorder in emergency room of Mataram District Hospitsl. It is recommended that training of pursed lips breathing be used to improve life quality of patients with respiratory disorder.